Sociopedagogic Dynamics in Teenager Interrelations - Barkauskaitė, Marija (Acta Paedagogica Vilnensia, 2002)
This article is intended to discuss and justify socio-educational evolution of V-VIII grade students of the general education schools, i.e., the relationship between the status of the classroom, to clusters creation, performance, security and a sense of family class, values, interests and change the dynamics of its relationship with the socio-cultural environment and changes in the education system. The article presents the most important factors in adolescent education study may reasonably be said that the adolescent socio-educational development is mainly determined by the societal socio-cultural, political and economic changes, respectively operating in the education system change, while teen relationships, activities and value orientations concept.
Keywords: Communication; teenagers' interrelations; peer group; status in the classroom.